ASUPAN ZAT GIZI DAN STATUS GIZI PADA REMAJA PUTRI DENGAN SINDROM PRA MENSTRUASI DI SMA NEGERI 1 KAKAS - Meildy E. Pascoal; Vera T. Harikedua; Kathlen Fredika Kirojan (POLTEKKES KEMENKES MANADO, 2015)
Adolescence is a transition period or the transition from childhood to adulthood, this period isalso often called puberty. One of the menendai puberty is menstruation. Young women arestill vulnerable to the occurrence of menstrual disorders, disorders of the one pre-menstrualsyndrome. Pre-menstrual syndrome is a condition when a number of symptoms occursregularly and is associated with the menstrual cycle. The symptoms that occur are physicaland emotional symptoms. The purpose of this study is to describe the nutrient intake andnutritional status of adolescent girls against pre-menstrual syndrome.This type of research isa descriptive cross-sectional design. Primary data was collected through interviews using aquestionnaire form Semi FFQ and pre-menstrual syndrome incidence was asked torespondents. While secondary data taken from school is a general overview of State HighSchool 1 Kakas.In this study, the intake of protein, carbohydrate, vitamin B6 and magnesiumwith more moderate levels of pre-menstrual syndrome. Unlike the fat intake in this study whowere mostly lack the level of pre-menstrual syndrome being. In this study the nutritionalstatus of respondents mostly normal with moderate levels of pre-menstrual syndrome. thelevel of pre-menstrual syndrome were found on the respondents in this study were mostlylevel that is equal to 72% or numbered 35 people.